Distribution and use of cash income from basket and mat crafting: implications for rural livelihoods in the Eastern Cape, South Africa. Issue 3 (2nd July 2016) - Adam, Y. O.; Shackleton, C. M.
Abstract: The objective of this paper was to investigate the extent to which baskets and mats local trade contributes to rural livelihoods of the crafters' household and community downstream income. Primary data were collected through structured interviews with 83 crafters from Noqhekwana village in Port St. Johns municipality using snowball sampling in May, 2015. The survey was supplemented by secondary data and direct observations. The findings show that crafting contributed 35% of crafter's household total income. The received income is spent on expenses in the household and downstream actors depending on the crafter's priorities. Lack of organization between crafters, access to sufficient raw material, and low prices were identified as major challenges involved in the production and trade of the products.